The Extent of Rent Sharing along the Wage Distribution - Alessia Matano; Paolo Naticchioni (Institute of Labor Economics (IZA), 2017)
The relation between rent sharing and wages has generally been evaluated on average wages. This paper uses a unique employer-employee panel database to investigate the extent of rent sharing along the wage distribution in Italy. We apply quantile regression techniques and control for national level bargaining, unobserved worker and firm heterogeneity and endogeneity. Our findings show that the extent of rent-sharing decreases along the wage distribution, suggesting that unskilled workers benefit most from firms' rents. By applying quantile regressions by occupational categories, we show that the decreasing pattern is mainly driven by blue collar workers, while estimates for white collars are higher and basically constant along the wage distribution. We also provide evidence that unions might represent one of the driver of our findings.
Keywords: C33; J31; J41; L25; 330; rent sharing; wage distribution; quantile regressions; IV quantile regressions; quantile fixed effects regressions